Fluorescence-based biosensor for monitoring of environmental pollutants: From concept to field application - Bidmanova, Sarka; Kotlanova, Marketa; Rataj, Tomas; Damborsky, Jiri; Trtilek, Martin; Prokop, Zbynek (Biosensors & bioelectronics, 2016)
An advanced optical biosensor was developed based on the enzymatic reaction with halogenated aliphatic hydrocarbons that is accompanied by the fluorescence change of pH indicator. The device is applicable for the detection of halogenated contaminants in water samples with pH ranging from 4 to 10 and temperature ranging from 5 to 60°C. Main advantages of the developed biosensor are small size (60×30×190mm(3)) and portability, which together with short measurement time of 1min belong to crucial attributes of analytical technique useful for routine environmental monitoring. The biosensor was successfully applied for the detection of several important halogenated pollutants under laboratory conditions, e.g., 1,2-dichloroethane, 1,2,3-trichloropropane and γ-hexachlorocyclohexane, with the limits of detection of 2.7, 1.4 and 12.1mgL(-1), respectively. The continuous monitoring was demonstrated by repetitive injection of halogenated compound into measurement solution. Consequently, field trials under environmental settings were performed. The presence of 1,2-dichloroethane (10mgL(-1)) was proved unambiguously on one of three potentially contaminated sites in Czech Republic, and the same contaminant was monitored on contaminated locality in Serbia. Equipped by Global Positioning System, the biosensor was used for creation of a precise map of contamination. Concentrations determined by biosensor and by gas chromatograph coupled with mass spectrometer exhibited the correlation coefficient of 0.92, providing a good confidence for the routine use of the biosensor system in both field screening and monitoring.
Keywords: hydrolasy; Biosensing Techniques; Halogenated pollutant; biosenzitivní techniky; Environmental monitoring; fluorescenční spektrometrie; Field-testing; Optical biosensor; Bacteria; fluorescence; voda; Dehydrochlorinase; Hydrolases; Environmental Monitoring; chlorované uhlovodíky; Spectrometry, Fluorescence; Fluorescence; Haloalkane dehalogenase; chemické látky znečišťující vodu; Water; Water Pollutants, Chemical; monitorování životního prostředí; Hydrocarbons, Chlorinated